Water of Increased Ionic Strength on Surface Interactions with Labradorite - Malibongwe S. Manono; Lisa L. October; Resoketswe M. Manenzhe; Kirsten C. Corin (Proceedings)
Labradorite is a beautiful and popular mineral known for its iridescent play of colour. It is commonly found in igneous rocks and belongs to the feldspar group of minerals which are common in sulfidic Cu-Ni-PGM ores in South Africa. Labradorite primarily consists of calcium, sodium, aluminum, and silicon. There are various uses for labradorite, these range from its use as an ornamental stone to being an additive in ceramics and in glassmaking. Therefore understanding its behaviour under various water conditions is therefore important not only for froth flotation where process water of high ionic strength is used but also important for the question of how ceramics with labradorite as an additive would be affected when subjected to water of high ionic strength and water containing Ca2+, Mg2+, Cl− and SO42− ions in significant quantities. This study therefore examined the behaviour of labradorite in changing water quality, specifically of increasing ionic strength. Labradorite particles were investigated for their behaviour under varying ionic strength of water using two techniques, namely the zeta potential analyser and UV-vis spectroscopy in order to understand the impact of water quality on surface chemistry of labradorite. The zeta potential analyser was used to understand effects on the surface charge of the mineral whilst UV-vis spectroscopy was used to determine the adsorption of sodium carboxymethyl cellulose (CMC) at the mineral surface. CMC was important in this study not only because of its use in flotation as a depressant but also due to its role in materials manufacturing as a binder and rheology modifier, both of which are significant properties in the production of ceramics and pellets. The results of this study showed that the adsorption of CMC, is enhanced in water of high ionic strength. It was also shown that the electrokinetic potential of labradorite increased and became less nagative in water of higher ionic strength, thus demonstrating a passivation effect at the labradorite mineral surface. The findings of this study imply that gangue minerals associated with or of a similar nature to labradorite, such as the feldspar group of minerals in sulfide ore flotation, are likely to be depressed in flotation. Furthermore, the results from this study may be valuable for the ceramics and glassmaking industries, where labradorite is used as an additive, especially in cases where their products are exposed to harsh water conditions.